2011
DOI: 10.4236/ti.2011.24029
|View full text |Cite
|
Sign up to set email alerts
|

Internal Control Disclosure and Corporate Governance: Empirical Research from Chinese Listed Companies

Abstract: The aim of this paper is to research the influence of corporate governance structure on internal control disclosure in a sample of 1309 Chinese listed nonfinancial companies in 2010. We discover that internal control disclosure is positively related to directors' remuneration, two part-time posts of chairman and general manager, directors' education level and supervisors' education level, and it negatively related to the proportion of state ownership. Internal control disclosure is not significantly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 8 publications
4
31
0
Order By: Relevance
“…Disclosure indices in the literature (Deumes and Knechel, 2008;Abraham and Cox, 2007;Van de Poel and Vanstraelen, 2011;Leng and Ding, 2011) are built mainly on checklists of items. We argue that these indices cannot capture the variety of content that management can disclose on the ICS.…”
Section: Insert Table 1 About Here 42 Measurement Of Ics Disclosurementioning
confidence: 99%
“…Disclosure indices in the literature (Deumes and Knechel, 2008;Abraham and Cox, 2007;Van de Poel and Vanstraelen, 2011;Leng and Ding, 2011) are built mainly on checklists of items. We argue that these indices cannot capture the variety of content that management can disclose on the ICS.…”
Section: Insert Table 1 About Here 42 Measurement Of Ics Disclosurementioning
confidence: 99%
“…Elbannan (2009) suggested that corporate governance strength is positively related to internal control quality in U.S. firms disclosing internal control weaknesses in their Securities and Exchange Commission filings. Leng and Ding (2011) aimed to research the influence of corporate governance structure on internal control disclosure. They discovered that internal control disclosure is positively related to directors' remuneration, two part-time posts of chairman and general manager, directors' education level and supervisors' education level, and it negatively related to the proportion of state ownership.…”
Section: Information and Communicationmentioning
confidence: 99%
“…To date, there have been a number of researches in developed and developing countries to measure corporate disclosure on financial and non-financial companies, for example: Al-Janadi, Rahman, and Omar (2013); Alves, Rodrigues, and Canadas (2012); Barako (2007) ;Bilal, Tufail, Khan, Abbas, and Saeed (2013);Botosan (1997) ;Fekete, Matis, and Lukács (2008); Healy and Palepu (2001); Hossain and Hammami (2009) ;Ianniello, Mainardi, and Rossi (2013); Jensen and Meckling (1976); Leng and Ding (2011);Li and Zhao (2011);Li and Qi (2008);Lokman (2011);Nandi and Ghosh (2013); Omran and Abdelrazik (2013);Rouf (2011);Sukthomya (2011);Vu (2012);Qu (2011);Lan, Wang, and Zhang (2013);. A few of their studies will be chosen to help understand the nature, methodology, and findings of this study.…”
Section: Literature Reviewmentioning
confidence: 99%